A contingency perspective of pro-organizational motives, unethical pro-organizational behavior, and organizational citizenship behavior - Cheng, Ken; Hu, Panpan; Guo, Limin; Wang, Yifei; Lin, Yinghui (Frontiers in Psychology, 2022)
Although the effects of pro-organizational motives on pro-organizational behaviors (i.e., unethical pro-organizational behavior and organizational citizenship behavior) and their boundaries have been explored to some extent, extant studies are rather piecemeal and in need of synthesis and extension. Based on prior motivational research on pro-organizational behaviors, we develop a comprehensive contingent model in which moral identity and impression management motives will moderate the links between pro-organizational motives, unethical pro-organizational behavior and organizational citizenship behavior. Adopting a time-lagged design, we collected data from 218 salespeople in an internet technology service company in China. Results showed that pro-organizational motives were positively related to unethical pro-organizational behavior and organizational citizenship behavior. Moral identity weakened the impact of pro-organizational motives on unethical pro-organizational behavior but strengthened the influence of pro-organizational motives on organizational citizenship behavior. Furthermore, we found that impression management motives strengthened the effects of pro-organizational motives on unethical pro-organizational behavior and organizational citizenship behavior and that the interaction of impression management motives and pro-organizational motives was stronger on unethical pro-organizational behavior than on organizational citizenship behavior. Theoretical and practical implications, limitations and future directions are discussed.